Seasonal wound presence and susceptibility to Neonectria ditissima infection in New Zealand apple trees - Amponsah, N.T.; Walter, M.; Beresford, R.M.; Scheper, R.W.A. (New Zealand Plant Protection, 2015)
Leaf scar wounds are important sites for Neonectria ditissima infection of apple trees Monitoring leaf fall in Scilate/Envy and Braeburn trees to estimate leaf scar wound presence showed maximum leaf scar incidence occurred in June (early winter) Wounds detected in New Zealand apple orchards were bud scale scars fruit thinning and picking wounds leaf scars and pruning cuts Picking wounds are caused during harvest where the pedicel is detached from the shoot Susceptibility of these different types of wounds was determined using artificial inoculation of N ditissima conidia during the season Pruning cut wounds were the most susceptible followed by fruit picking and thinning wounds and the least susceptible were leaf scar wounds No infections were observed when bud scale wounds were inoculated There was no difference in wound susceptibility between cultivars but overall Scilate/Envy wounds developed more lesions than Braeburn wounds